Institutional Dynamics of Islamic Religiuos Education (Integrated Islamic Schools) in Indonesia - Iwantoro, Iwantoro; Faridi, Faridi; Humaidi, Nurul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to describe the dynamics of Integrated Islamic Schools in Indonesia, starting from the background of the emergence to the philosophical concepts and curriculum used. This research method uses a qualitative approach with a literature research approach. Data were obtained from references of research journals, related books, and websites. The results of this study indicate that the emergence of Integrated Islamic Schools (SIT) was motivated by the community's need for a complete education by balancing general knowledge with the cultivation of Islamic values. In addition, SIT has a mission of da'wah in it by preparing a young generation of Muslims who are strong and ready to preach. The curriculum used is the curriculum from the Ministry of Education and Culture combined with Islamic values so that there is an integration between general knowledge and Islamic knowledge